2023
DOI: 10.1177/11771801231197979
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural identity of Indigenous Salasacas in Ecuador

Pablo Lamino Jaramillo,
Amy E Boren-Alpízar

Abstract: Latin America’s Indigenous are as varied as the place they live in and focus on past, beliefs, and culture. In Ecuador, the Indigenous Salasacas are famous for being strict in their cultural preservation, language, customs, agricultural practices, and costumes, which are considered unique. This ethnographic study aimed to understand the Salasacas’s agricultural identity across different generations and reports the experiences and perceptions of 12 Salasacas participants. Participants reported that many Salasac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Other studies have shown the potential of agricultural education to reduce young people's intentions to migrate (Rhoda, 1983). When encouraging agricultural education as a future career path, the growing and acute trend of the unwillingness of young people to work in agriculture must be considered (Girdziute et al, 2022;Lamiño Jaramillo et al, 2023), or the perception of migration as a better option will lead to migratory behavior (Migali & Scipioni, 2018). Finally, similarly to (Lamiño Jaramillo et al, 2021), this study continues the development of national profiles on youth migration that could serve to inform local, national, and regional initiatives contributing to inform inclusive and effective mechanisms to cultivate the future agricultural workforce for future generations in low-and middle-income countries.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Other studies have shown the potential of agricultural education to reduce young people's intentions to migrate (Rhoda, 1983). When encouraging agricultural education as a future career path, the growing and acute trend of the unwillingness of young people to work in agriculture must be considered (Girdziute et al, 2022;Lamiño Jaramillo et al, 2023), or the perception of migration as a better option will lead to migratory behavior (Migali & Scipioni, 2018). Finally, similarly to (Lamiño Jaramillo et al, 2021), this study continues the development of national profiles on youth migration that could serve to inform local, national, and regional initiatives contributing to inform inclusive and effective mechanisms to cultivate the future agricultural workforce for future generations in low-and middle-income countries.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%